A new unusual-looking Cyrtochilum (Orchidaceae) from Sierra Nevada de Santa Marta in Colombia - Dalström, Stig (Universidad de Costa Rica, 2020)
A new and unusual-looking Cyrtochilum species is described, compared with the possibly closely related Cyrtochilum leucopterum and illustrated by drawings and a photograph of the holotype. It is distinguished from Cyrtochilum leucopterum by having an elongate basal portion of the lip with erect lateral lobes, and a trilobed front lamina with a glabrous, blunt and thickened bilobed lip callus, versus what appears to be more horizontally spreading lateral lip lobes, and a densely micro-pubescent apically multifid lip callus for the latter species. The new species also has some purported silica bodies of unknown significance visible in plant and flower parts, which are not present in C. leucopterum. Key Words: Colombia, Cyrtochilum leucopterum, Helmuth Schmidt-Mumm, Oncidiinae, new species